Synthesis of pyridazine derivatives by Suzuki-Miyaura cross-coupling reaction and evaluation of their optical and electronic properties through experimental and theoretical studies - Fernandes, S. S. M. (2018)
A series of π-conjugated molecules based on pyridazine and thiophene heterocycles 3a-e were synthesized using commercially or readily available coupling components, through a palladium catalyzed Suzuki-Miyaura cross-coupling reaction. The electron-deficient pyridazine heterocycle is functionalized by a thiophene electron-rich heterocycle at position 6 and different (hetero)aromatic moieties (phenyl, thienyl, furanyl) are functionalized with electron acceptor groups at position 3. DFT calculations were carried out to obtain information on the conformation, electronic structure, electron distribution, dipolar moment, and molecular nonlinear response of the synthesized push-pull pyridazine derivatives. Hyper-Rayleigh scattering in 1,4-dioxane solutions using a fundamental wavelength of 1064 nm was used to evaluate their second-order nonlinear optical properties. The thienylpyridazine functionalized with the cyano-phenyl moiety exhibited the largest first hyperpolarizability (beta = 175 × 10-30 esu, using the T convention) indicating its potential as a second harmonic generation (SHG) chromophore.